Flow rate variation and biological agents that obstruct drippers of swine effluent - Batista, Rafael Oliveira; Oliveira, Rubens Alves de; Cunha, Maria Elidayane da; Cunha, Rutilene Rodrigues da; Portela, Jeane Cruz; Gurgel, Marcelo Tavares (Comunicata Scientiae, 2018)
Emitter clogging is the major problem of drip irrigation systems operating with wastewater. The objective of this study was to evaluate the alteration of the flow rate variation coefficient (FVC) and to identify the biological agents that cause obstruction in drip units operating with swine effluent and public water supply. The experiment was set up in a split-plot scheme, with the times of application of swine effluent and public water supply in the main plots and dripper types in the secondary parcels, evaluating times of FVC in the tertiary parcels, using a completely randomized design (CRD) with three repetitions. The FVC of the drip subunits was calculated on every 40 hours as well as the microscopic analysis of the biological agents of clogging, until 160 h. At the end of the tests, biofilm samples were collected in each drip unit to identify the groups of predominant bacteria. The results indicated that the FVC was effective in detecting the clogging of the emitters, evidencing that the construction characteristics and the times of application of swine effluent and of the public water supply interfere in this process. Microscopic analyzes of the biofilm indicated that the main biological agents that caused obstruction were algae, bacteria, fungi and protozoa.